Analysis the Impact of Exchange Rate Fluctuations on the Consumer Price Index in Syria During the period 2011 - 2017 (Damascus University Journal for the economic and Political sciences, 2021)
This research presents a technical and economic analysis of factors that led to fluctuations in the exchange rate and the consumer price index during 2011-2017.typical study was also conducted to prove and explain correlation &causality relationship and its direction between those two variables .by using EViews software and based on monthly data of the two variables during the study period from official and non-official sourcesThe results refer to economic and non-economic factors largely overlapped to determine exchange rate and consumer price index during the study period Where Syrian pound has lost more than 90% of its value. Which causes a sharp rise in the prices of the consumer basket components that doubled between 3-16 times by the component .As a result, the Syrian economy has entered stagflation resulted from the imbalance between the money supply and the real economy at the same time with a general weakness of domestic demand.On the other hand, the econometric result shown that the exchange rate fluctuations and decline in the Syrian Pound value considered the major causes to rise in the consumer price index in Syria during the study period beside other minor factors. That explained by the exposed of Syrian economy to the outside world due to its almost absolute dependence on imports to meet the needs of basic commodities in light of the decline and inadequacy of local production. The sanctions also contributed to the increase in import costs, which included freight costs, external insurance, remittance costs, documentary credits and commission rates, due to the need to enter many parties into transactions and circumvent sanctions.
Keywords: Exchange Rate; Consumer Price Index; Inflation